Implementation of The Convergence Program to Accelerate Stunting Reduction in Sibolga City - Putra Apriadi Siregar; Rani Suraya; Syamsu Rizal Lubis; Muhammad Ancha Sitorus; Ashela Risa (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Sibolga City is one of the priority cities in the effort to accelerate stunting reduction. Sibolga City implements an accelerated stunting prevalence reduction program that involves cross-sectors, better known as the convergence action to accelerate stunting reduction. The purpose of the study was to evaluate the implementation of the convergence program to accelerate stunting reduction in Sibolga City. This research is a qualitative study involving 18 informants from  Regional Work Units  that are members of the Sibolga City  Stunting Reduction Acceleration Team. This research was conducted in November 2023 in Sibolga City, which consists of 4 sub-districts and 17 villages. Data were collected by conducting Focus Group Discussions and in-depth interviews. Furthermore,  Data is analyzed through triangulation of methods, sources, and between researchers. The results of the analysis of the effectiveness of the program show that the quality of human resources and financing sources is good enough to reduce the stunting rate in the kelurahan which is the locus of stunting. Likewise, the results of the analysis of the program implementation process. The program planning that was prepared was in accordance with the problems obtained in the situation analysis and had targeted the locus villages determined in the situation analysis. The implementation and evaluation process has also been carried out well, which ultimately has an impact on reducing the stunting prevalence rate by 11.3%. As an effort to encourage a greater reduction in stunting prevalence, we recommend that the Sibolga City Government increase human resource capacity and funding, encourage the involvement of various parties including the private sector in accelerating stunting reduction programs in Sibolga City, improve coordination between Regional Work Units in the planning, implementation and evaluation processes and encourage the availability of a quality and sustainable data management system in each villageKeywords: Accelerate, Convergence, Reduction, Prevalence, Stunting